The Effect of Website-Based Learning ‘Belajar Lagu Daerah’ on Elementary School Students’ Understanding of Regional Songs: Pengaruh Pembelajaran Berbasis Website “Belajar Lagu Daerah” terhadap Pemahaman Lagu Daerah pada Siswa Sekolah Dasar - Tiwi Aini; Julia Julia; Dety Amelia Karlina (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2025)
The dominance of popular digital media has contributed to declining interest in Indonesia’s traditional songs among elementary pupils. This study examines the effect of the BELANDA (Belajar Lagu Daerah) website on students’ understanding of traditional songs. Using a quasi-experimental nonequivalent control group design, two grade-5 classes (n=27 per class) at SD Negeri Situraja participated. The experimental class used the BELANDA website for three sessions, while the control class received conventional instruction. Pretest–posttest data were analyzed via descriptive statistics, assumption checks, paired and independent t-tests, and normalized gain (N-Gain). Results indicate a significant improvement in the experimental class compared with the control (p<.05), with mean N-Gain of 0.70 (high) versus 0.45 (medium), respectively. Findings suggest that interactive, audiovisual web-based materials can strengthen cognitive understanding of local cultural elements among elementary students.